Redesigning Digital Marketing Strategy for Increasing Sales of Small Business: A Case Study in Pinescarf - Nadhilah Husna; Hartoyo Hartoyo; Nur Hasanah (Bina Nusantara University, 2024)
The research provided a complete and practical perspective on reviving struggling small businesses by redesigning marketing strategies to boost sales. It aimed to identify the implemented marketing strategy, evaluate the marketing performance, and redesign the marketing strategy. An exploratory mixed-method approach was applied, comprising three stages. First, qualitative descriptive analysis identified the existing marketing strategy through in-depth interviews and direct observation, analyzed using Segmentation, Targeting, and Positioning (STP) and the Cocreation, Currency, Communal Activation, and Conversation (4C) marketing mix. Second, ongoing marketing performance was evaluated based on the perceptions of 267 Instagram and Shopee followers of Pinescarf, using convenience sampling and the Aware, Appeal, Ask, Act, and Advocate (5A) customer path concept. Third, strategy formulation utilized the Analytical Hierarchy Process (AHP), integrating qualitative and quantitative approaches based on insights from management, consumers, and industry experts. The identification process shows that Pinescarf needs to improve its implementation of the 4C marketing mix. A bottleneck at the Act and Advocate stages prevents purchases, resulting in a funnel-shaped customer path. Strategy formulation using AHP prioritizes increasing sales as main marketing objective of Pinescarf. Maximizing advertising performance in the conversation mix is the first priority, followed by regular discounts in the currency mix to address the Act stage bottleneck. These findings can help Pinescarf to save time and costs by focusing on effective marketing efforts. Additionally, the research has connected marketing theory with real-world practice, enabling businesspeople to make informed decisions based on solid analysis alongside their existing intuition.